Al-doped maghemite examined as catalyst for the discoloration of methylene blue and for the decomposition of ammonium nitrate - Cabrera, Alejandra Fabiana (2023)
Nanostructured aluminium-doped magnetic iron (III) oxide (AlxFe2-xO3 with x= 0.33, 0.67 and 1) have been prepared by autocombustion method. The as-prepared samples were characterized by XRD, thermogravimetric analysis, UV-vis and Mössbauer spectroscopies and magnetometry. The cubic spinel is the main crystalline phase for all compositions. The presence of Al in the spinel phase causes a progressive decrease in both the cell parameter (a) and the grain size (L). The room temperature Mössbauer spectrum of x= 0.33 is mainly composed of a Fe3+ broad sextet while, for higher Al content, the spectra consist of a Fe3+ broad doublet corresponding to superparamagnetic maghemite. The saturation magnetization decreases with the Al doping and reaches a rather low value for the illcrystalline sample x = 1 (MS ~ 2 emu/g). The optical direct band gap of the samples is red-shifted with respect to pure maghemite, with values close to 2 eV. The photocatalytic performance of AlxFe2-xO3 tested in the decolorization of methylene blue dye showed a good efficiency for the oxide whose band gap energy best matches the energy of the incident light (x= 0.33). The catalytic effect of these samples on the thermal decomposition of ammonium nitrate is more noticeable for those Al concentrations that lead to the reaction being exothermic.